Substantiation of the choice diversification strategy for ensuring the safety of the enterprise activity - Ignatyuk, A.; Khumarova, N.; Vitrenko, A.; Kuzmenko, O.; Koptieva (Fadieieva), H. M.; Doroshenko, A. (Blue Eyes Intelligence Engineering and Sciences Publication, India, 2019)
The development of diversification enables the enterprise to provide economic security, achieve competitive advantages and minimise the risks of its activities. The research in the article is divided into three main blocks: In the first, the theoretical foundations for substantiating the choice of strategy for diversification of the production enterprise were summarized. The second proposes a methodologyof technology of choice of production strategies for ensuring the safety of the enterprise activity. The third block contains the development of recommendations to justify the choice of diversification strategy:the mechanism of formation and realization of diversification policy of the enterprise is offered;the use of the peer review method to justify the choice of diversification strategy is clearly presented (possible directions of strategy of diversification of activity are identified and the most promising directions of strategy of diversification of activity of investigated enterprise are selected by the method of a priori ranking);developed the methodological foundations for managing the diversification strategies of an industrial enterprise, which is a necessary element of the systematic support of the strategy of diversification of the enterprise activity (proposed an integrated algorithm for managing the diversification strategies of industrial enterprises; a fragment of the matrix of the choice of the type of diversification was developed, based on the goals and motivational reasons;the hierarchical structure of the decision-making system for the choice of rational diversification strategy is proposed and the scale of values of confidence coefficients is developed.
Keywords: enterprise activity; diversification; safety; strategy